Costs and import costs of past, present, and future TB drug regimens: a case study for Karakalpakstan, Uzbekistan - Kohler, Stefan; Sitali, Norman; Achar, Jay; Paul, Nicolas (Journal of public health, 2023)
Tuberculosis (TB) drugs and their import are costly. We assessed how shorter TB drug regimens, which were non-inferior or superior in recent TB trials, can affect the costs for purchasing and importing TB drugs.We estimated the drug costs and import costs of 39 longer and shorter TB drug regimens using TB drug prices from the Global Drug Facility and import cost estimates for a TB program in Karakalpakstan, Uzbekistan. Drug regimens from recent TB trials were compared with TB drug regimens following present or past World Health Organization recommendations.We estimated an import cost of $4.19 and a drug cost of $43 per standard 6-month drug-sensitive (DS)-TB regimen. A new 17-week DS-TB regimen from the TBTC Study 31 currently requires more tablets and is more expensive to import ($6.08) and purchase ($233). The TB program can substantially decrease import costs ($2.26-14) and drug costs ($391-2308) per multidrug-resistant (MDR)-TB regimen when using new 6-month or shorter drug regimens from the Nix-TB, NExT, TB PRACTECAL, ZeNix, or BEAT TB trials instead of 9-20-month regimens with import costs of $9.96-507 and drug costs of $354-15 028. For a commonly used 20-month all-oral, bedaquiline-containing MDR-TB regimen, we estimated costs of $41 for drug import and $1773 for drug purchase.The implementation of a new and shorter DS-TB regimen may increase the costs for drug purchase and import. The implementation of new and shorter MDR-TB regimens may decrease the costs for drug purchase and/or drug import.